Innate immunity in cardiac myxomas and its pathological and clinical correlations. Issue 1 (January 2018) - Di Vito, Anna; Santise, Gianluca; Mignogna, Chiara; Chiefari, Eusebio; Cardillo, Gabriella; Presta, Ivan; Arturi, Franco; Malara, Natalia; Brunetti, Francesco; Donato, Annalidia; Maisano, Domenico; Leonetti, Stefania; et al.
Cardiac myxomas are the most common benign cardiac tumor. We investigated the immunohistochemical properties of 11 surgically excised cardiac myxomas, in order to analyze the correlation between macrophages and mast cell populations and clinical parameters. CD68 + /CD163 − /iNOS − (M0) cells represent the most abundant macrophage phenotype; however, CD68 + /CD163 + cells (M2) were also frequent. CD68 + /iNOS + (M1) elements were rare. Mast cells, defined as a population of c-kit (CD117) + and/or tryptase + cells were also detected. Statistical analysis showed significant correlations between c-kit (CD117) + and tryptase, CD68 and erythrocyte sedimentation rate (ESR), ESR and red blood cell count (RBC), and prothrombin time and platelet count. The inverse correlation between RBCs in peripheral blood and ESR suggested that anemia associated with chronic inflammatory disease is a noncasual event in patients suffering from cardiac myxoma. Mechanical hemolysis may be only a minor component of anemia, according to the lack of correlation between echographic surface and RBCs. Moreover, tumor size did not correlate with ESR, showing that inflammatory state may depend from both tumor cells population and inflammatory infiltrate. In the future, modulation of macrophage polarization in cardiac myxomas might represent important therapeutic target.